Application of Machine Learning in Predicting E-Commerce Market Trends - Brandon Kandow; Noah Paulus Legi; Shevchenko S. Tumbo; Leonardo Valen Tumbelaka; Putri Angellita; Deitje Sofie Pongoh (Syntax Corporation Indonesia, 2025)
The findings show that this technology enhances customer satisfaction and business profitability. However, challenges related to data privacy and the complexity of implementing algorithms remain critical concerns. This article provides insights into the opportunities and challenges of applying machine learning in e-commerce, which is increasingly crucial to the industry's development. The rapid growth of e-commerce has led to an overwhelming amount of data, making it essential for businesses to adopt advanced technologies such as machine learning (ML) to analyze and predict market trends. This study explores the application of machine learning techniques in predicting consumer behavior, sales patterns, and emerging market trends in the e-commerce industry. Various ML models, including supervised learning algorithms (linear regression, decision trees, and neural networks) and unsupervised learning techniques (clustering and anomaly detection), are evaluated for their effectiveness in analyzing large-scale e-commerce data. The research findings indicate that ML-driven predictions significantly enhance demand forecasting, personalized recommendations, and inventory management, leading to increased sales efficiency and improved customer satisfaction. However, challenges such as data quality, computational complexity, and ethical concerns related to consumer privacy and bias in algorithms must be addressed for optimal implementation. By leveraging machine learning, businesses can make data-driven decisions, optimize marketing strategies, and stay ahead of competitive market dynamics.